A theoretical model of factors reallocation before a tourism demand shock - Rojas, Diego (2014)
This paper analyzes the relevance and possible impact of tourism on Costa Rican economy, from a theoretical point of view. The absence of formal studies assuming conditions close to the Costa Rican economy and the wide application of incentives in this nation to promote tourism prove this research relevant. First, the different models proposed in the literature are analyzed. Secondly, a model close to Costa Rican conditions is developed. The development of such model is the main objective of this paper. Specifically, the objective of this model is to shed some light on the following questions: 1) What is the possible impact on domestic production –in the long run- of an permanent increase in tourism demand for domestic goods?, 2) In the long run, what sectors might increase their production and what sectors might experience a decrease in production before a tourism demand increase? and, 3) What is the expected behavior of relative prices –in the long run- before an increase in tourism demand?